1998
DOI: 10.1046/j.1365-2249.1998.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative cytokine release during coronary artery bypass grafting in patients of different ages

Abstract: Surgical interventions and cardiopulmonary bypass (CPB) induce a systemic inflammatory response with cytokine release. Ageing is perceived as a process of impaired immune functions: IL-1beta, IL-6 and tumour necrosis factor-alpha (TNF-alpha) secretion are increased while IL-2 release is reduced in advanced age. At present, little information is available about perioperative immune reactions at different stages of ageing. The aim of the present study was to compare IL-6, IL-1beta, TNF-alpha, IL-10 and soluble I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…Consistent with our previous reports on perioperative cytokine release and the results of other studies, peak concentrations of IL‐6, TNF‐ α and IL‐1 β were found on the day of surgery after operation [32–34]. On the first and second postoperative days, serum concentrations of sIL‐2R were significantly elevated compared to pre‐ and intra‐operative values.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our previous reports on perioperative cytokine release and the results of other studies, peak concentrations of IL‐6, TNF‐ α and IL‐1 β were found on the day of surgery after operation [32–34]. On the first and second postoperative days, serum concentrations of sIL‐2R were significantly elevated compared to pre‐ and intra‐operative values.…”
Section: Discussionsupporting
confidence: 91%
“…The release pattern of both CRP and SAA in our control patients has been observed by others. [31][32][33][34][35][36] The increase in CRP and SAA over time was significantly reduced in patients receiving GIK.…”
Section: Discussionmentioning
confidence: 99%
“…Study design, cardiopulmonary bypass technique and cytokine determinations were identical to those described previously [13].…”
Section: Methodsmentioning
confidence: 99%